1985
DOI: 10.1007/bf00450219
|View full text |Cite
|
Sign up to set email alerts
|

Instability of the cervical spine after anterior interbody fusion

Abstract: Twenty-one patients suffering from cervical spondylosis and peripheral symptoms underwent uncomplicated anterior interbody fusion of the cervical spine and were re-examined clinically and radiologically at 27 +/- 15 months (mean +/- SD) after the operation. Translatory displacement of the segment adjacent to the fusion level was noted in 14 patients. Its incidence could not be related to the age and sex of the patient, to extent of the fusion, or to postoperative time. Anterior slippage did not correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, controversy remains as to whether these conditions are related to altered biomechanics [ 5 7 8 9 10 11 ] or represent the natural history of cervical spondylosis at the adjacent segment [ 12 13 14 ]. Clearly, patients who have undergone cervical fusions are at an increased risk of developing ASP.…”
Section: Introductionmentioning
confidence: 99%
“…However, controversy remains as to whether these conditions are related to altered biomechanics [ 5 7 8 9 10 11 ] or represent the natural history of cervical spondylosis at the adjacent segment [ 12 13 14 ]. Clearly, patients who have undergone cervical fusions are at an increased risk of developing ASP.…”
Section: Introductionmentioning
confidence: 99%
“…When discussing ASP, it is important to differentiate between radiographical ASP, which is radiographical evidence of degeneration at the levels adjacent to a previous fusion, and clinical ASP (CASP), which is the development of clinically relevant symptoms (i.e., radiculopathy and/ or myelopathy) that correlate with radiographical evidence of degeneration that is adjacent to a previous fusion [ 2 ]. The prevalence of CASP during the current follow up periods of 4.5 years and 21 years are 25%-89% [ 3 , 4 , 5 ] and 7%-15%, respectively [ 1 , 6 , 7 , 8 ]. Several factors have been associated with the development of ASP, such as the number and location of fusion segments, age, and pre-existing degenerative changes at adjacent segments [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CASP during the current follow up periods of 4.5 years and 21 years are 25%-89% [ 3 , 4 , 5 ] and 7%-15%, respectively [ 1 , 6 , 7 , 8 ]. Several factors have been associated with the development of ASP, such as the number and location of fusion segments, age, and pre-existing degenerative changes at adjacent segments [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, degenerative progression of an adjacent segment can be prevented, and reestablishment of cervical curvature aided 20. Thereby, complications related to anterior cervical decompression and fusion encourage the use of cervical arthroplasty as an alternative to fusion surgery 21,22,23,24,25,26. Nevertheless, many studies that have conducted radiographic follow-up review of patients treated by arthroplasty and fusion have demonstrated disappointing clinical results 27,28…”
Section: Discussionmentioning
confidence: 99%